L1 CRISPR/Cas9 specific editing of the mutant huntingtin allele. (13th September 2016) - Monteys, Alejandro Mas; Ebanks, Shauna A; Keiser, Megan S; Davidson, Beverly L
Abstract : Background: Huntington's disease (HD) is a fatal dominantly inherited neurodegenerative disorder caused by CAG repeat expansion (>36 repeats) within the first exon of the huntingtin gene. Although mutant huntingtin (mHTT) is ubiquitously expressed, the brain shows robust and early degeneration. Current RNA interference-based approaches for lowering mHTT expression has been efficacious in mouse models, but basal mutant protein levels are still detected. Aim: Our goal is to fully mitigate expression from the mutant HTT allele using a gene editing approach with the CRISPR/Cas9 system. Methods/techniques: We designed several sgRNA sequences that bind and recruit Case protein to prevalent promoter-resident single nucleotide polymorphisms (SNP) contained within PAM sequences flanking HTT-exon1. Results: Allele specific targeted deletions of the mutant HTT allele were generated when SNPs are present in heterozygosity with the mutant HTT allele. Mutant HTT protein was terminated both in vitro after transfection of fibroblast lines from patients, and in vivo after viral delivery in a mouse model of HD. Conclusion: Single nucleotide polymorphisms present in heterozygosity and positioned within the PAM motif can be used for gene editing of a single allele.